Nepal measles outbreak response immunization during COVID-19: A risk-based intervention strategy. Issue 20 (3rd May 2022) - Bose, Anindya Sekhar; Rai, Pasang; Gupta, Binod Prasad; Pradhan, Rahul; Lacoul, Mona; Shakya, Sushil; Shrestha, Dipesh; Gautam, Abhiyan; Bhandari, Bharat; Shrestha, Basanta; Tinkari, Bhim Singh; Jha, Runa; et al.
Abstract: In 2020, National Immunization Programme (NIP) of Nepal implemented a measles outbreak response immunization (ORI) campaign, which was additional to an ongoing preventive measles-rubella SIA campaign. Both campaigns were implemented during ongoing COVID-19 transmission. By April, 220 measles cases and two deaths were confirmed from eight districts of Nepal. The NIP triangulated information from surveillance (measles and COVID-19), measles immunization performance and immunity profile, programme capacities and community engagement and applied a logical decision-making framework to the collated data to inform 'Go/No-Go' decisions for ORI interventions. This was reviewed by the National Immunization Advisory Committee (NIAC) for endorsement. Outbreak response with non-selective immunization (ORI), vitamin-A administration and case management were implemented in affected municipalities of four districts, while in the remaining districts outbreak response without ORI were undertaken. The structure and iterative application of this logical framework has been described. ORI was implemented without interrupting the ongoing measles-rubella vaccination campaign which had targeted children from 9 to 59 months of age. The age group for ORI was same as SIA in one sub-district area, while for the other three sub-district areas it was from 6 months to 15 years of age. More than 32, 000 persons (97% coverage) were vaccinated in ORI response. Overall measles incidence decreased by 98% after ORI. The daily incidence rate of measles was 94 times higher (95% confidence interval: 36.11 – 347.62) before the ORI compared to two weeks after ORI until year end. Close attention to surveillance and other data to inform actions and seamless collaboration between NIP and core immunization partners (WHO, UNICEF), with guidance from NIAC were key elements in successful implementation. This was an example of feasible application of the global framework for implementation of a mass vaccination campaign during COVID-19 through application of a simple decision-making logical framework.